2017
DOI: 10.1155/2017/4352783
|View full text |Cite
|
Sign up to set email alerts
|

Families Living with Blood-Borne Viruses: The Case for Extending the Concept of “Serodiscordance”

Abstract: The concept of “serodiscordance” (mixed infection status) is primarily associated with epidemiological concerns about HIV transmission risk in couples. We make the case for extending this concept to include families with mixed HIV and viral hepatitis status. Social research on couples with mixed HIV and hepatitis C status has laid an important foundation for illuminating how experiences of serodiscordance within intimate partnerships are much broader than concerns about risk. This body of work attests to serod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 98 publications
0
15
1
Order By: Relevance
“…Our study repeatedly endorsed the essential role of spouses/partners and the family as a whole in CHB management. The previous literature consistently acknowledged families as a crucial source of support for those with viral infections, and patients often depend on their primary relationships for supports in the inadequate medical care infrastructure, especially in family-oriented societies like Vietnam [20]. In addition, CHB requires a long-term treatment which may impose a substantial financial burden on patients and their families [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study repeatedly endorsed the essential role of spouses/partners and the family as a whole in CHB management. The previous literature consistently acknowledged families as a crucial source of support for those with viral infections, and patients often depend on their primary relationships for supports in the inadequate medical care infrastructure, especially in family-oriented societies like Vietnam [20]. In addition, CHB requires a long-term treatment which may impose a substantial financial burden on patients and their families [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…To measure stigma and discrimination, we referred to the Substance Abuse Self-Stigma Scale by Luoma et al [18], and adapted the conceptual framework by Parker and Aggleton which is used to measure stigma against the MMT (methadone maintenance treatment) and HIV/AIDS population [19]. The previous literature suggested that HIV and HBV infections share various characteristics including transmission routes, social stigma, and impacts on marginalized communities [20]. The final tool included four dimensions: (1) Blame/Judgment; (2) Shame; (3) Discrimination in various settings (workplace, healthcare services, family, and community); (4) Disclosure of CHB status.…”
Section: Methodsmentioning
confidence: 99%
“…Research has highlighted the practical, social, and political impact of HIV, HBV, and HCV on families, including economic security, caregiver stress, and culturally specific interpretations (Cotler et al, 2012; Hu, 2008; Ma et al, 2011; Owiti et al, 2015; Rodrigue et al, 2009; Rotheram-Borus et al, 2005). This suggests that family members also live with stigmatized, transmissible viral infections in their own right (Persson et al, 2017). As the role of families in the management of these infections is often hidden, especially in the recognition that forms of informal care are often invisible to support services (Hamilton et al, 2018; Neufeld et al, 2008), it is not surprising that families’ own support needs tend to be elided in public health responses because of the emphasis on transmission risk that has characterized the concept of serodiscordance to date.…”
Section: Who Is Living With Stigmatized Infectious Disease?mentioning
confidence: 99%
“…In short, any experience of HIV, HBV, or HCV is fundamentally relational (DeMatteo et al, 2002), not only in how these blood-borne viruses are acquired, transmitted, or prevented but also, as we have argued elsewhere, “because they are inexorably enacted, perceived, and managed through a range of socially situated relationships, meanings and practices” (Persson et al, 2017). There is a strong case, then, for the concept of serodiscordance to be expanded to capture wider familial relations and to recognize the complex and contingent socio-emotional dynamics of family engagement (Persson et al, 2017). Accordingly, one of the tasks at hand is capturing and interpreting the ways that people define family in the context of living with socially stigmatized blood-borne viruses.…”
Section: Who Is Living With Stigmatized Infectious Disease?mentioning
confidence: 99%
See 1 more Smart Citation